(3GdbhGfjf GdJi jSJYedgG GdefLe aj GSJfHGW GdbVGA ef GdfLhes - (3CMeO Hf eMeO Hf YHO GdLdjd GdSLRj, CHh SYjO,J (B477 (3g` s
(3ChdgG (B:s
(3bGd GdSLRi GdegfOS fQjO Cf fPcQ GdbhGfjf GdJi jSJYedgG GdefLe ai GSJfHGW GdbVGA ef GdfLhe hJLOjOgG Ydi ePgH CUMGH gPg GdUfGYI s
(3BNQgG (B:s
(3ahGLH Cf jSJYed GdbjGS ai SGFQ MGdGJ GdehGdjO hGdJMhjd hEMOGK GdMb hGdCeWGQ hGdOhd hGdedc hEdi gPG GdehVY jced Gdbhd ai GdbhGfjf hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B205(3H (B- (3U(B208(3Hs
(3ai fSN CNQi YfhGfg (B: (3JMUjd GdbhGfjf dGSJfHGW GdCMcGes
(3cJHJ Hbde eged GdfbW CMjGfGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B80s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B246 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B388 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs